Composite material for industrial sewage treatment as well as preparation method and application of composite material
By combining carbon nanotubes with iron, zinc, titanium modification and concave and concave rock stones, we form an efficient composite material, solving the problems of low efficiency and high cost in industrial wastewater treatment, and achieving efficient removal of heavy metal ions and sustainable wastewater treatment sex.
Patent Information
- Application Number
- CN202411682088.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The existing composite materials are inefficient in industrial wastewater treatment, have high material and preparation costs, and are insufficient in stability and reproducibility during the treatment process, making it difficult to meet the requirements of greening and sustainable development.
The preparation method of composite materials combining carbon nanotubes with iron-zinc-titanium modification and concave-blocking razor stone is adopted. The adsorption characteristics are enhanced through iron-zinc-titanium modification, carboxymethyl chitosan modification increases dispersion, and recyclability is improved through hydrogen bond self-assembly , form efficient industrial wastewater treatment materials.
It realizes efficient removal of heavy metal ions, reduces the concentration of organic pollutants in the water, improves the sewage treatment efficiency and suspended removal capacity, and has strong renewable materials, suitable for large-scale production, and reduces energy consumption and operating costs.
Smart Images

Figure CN119240847A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental protection, and in particular to a composite material for industrial sewage treatment and a preparation method and application thereof. Background Art
[0002] Industrial wastewater often contains a large amount of organic matter, heavy metal ions, suspended solids and other substances that are harmful to the ecological environment. If these wastewaters are discharged directly without treatment, they will cause serious water pollution, damage the ecosystem and endanger human health. Therefore, the development and application of efficient and economical wastewater treatment methods are crucial to achieving sustainable development and improving the utilization rate of water resources.
[0003] The application of composite materials in industrial wastewater treatment stems from their superior physical and chemical properties and good adaptability. By rationally designing the composition and structure of composite materials, the efficiency of wastewater treatment can be significantly improved, such as removing pollutants in water through adsorption, catalysis, membrane separation and other methods. This new material is used in wastewater treatment, which can not only improve the pollution removal ability, but also reduce energy consumption and operating costs during the treatment process, which is in line with the current trend of energy conservation and emission reduction.
[0004] In the field of industrial wastewater treatment, composite materials are increasingly used, especially in the removal of heavy metal ions, organic matter degradation and microbial degradation. In recent years, researchers have developed a variety of composite materials for different types of wastewater, such as polymer-inorganic composite materials, activated carbon composite materials and porous materials. These composite materials can effectively remove pollutants in wastewater due to their excellent adsorption properties and large specific surface area.
[0005] Although composite materials have made significant progress in industrial wastewater treatment, they still face many challenges and problems in practical applications. For example, the preparation cost of composite materials, the difficulty of large-scale production, the stability and regeneration during the treatment process, and the low efficiency of wastewater treatment are all technical bottlenecks that need to be broken through; green and sustainable development will become important considerations. In the preparation process of materials, avoid the use of chemicals that are harmful to the environment, and strive to develop environmentally friendly materials to reduce the negative impact on the ecology. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a composite material for industrial wastewater treatment and a preparation method and application thereof, so as to solve the technical problems of low wastewater treatment efficiency and high material and preparation costs of the current composite materials.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] The present invention provides a method for preparing a composite material for industrial wastewater treatment, comprising the following steps:
[0009] S1, adding carbon nanotubes to a mixed solution of ferrous sulfate and zinc chloride, then dropping a tetrabutyl titanate solution, heating, adding a NaOH solution under stirring, and continuing to stir for a period of time, then filtering, washing, drying, and calcining to obtain iron-zinc-titanium modified carbon nanotubes;
[0010] S2, soaking the iron-zinc-titanium modified carbon nanotubes in a hydrogen peroxide solution for a period of time, then adding carboxymethyl chitosan, dicyclohexylcarbodiimide and N-hydroxysuccinimide, ultrasonically treating, washing and drying the generated product to obtain modified carbon nanotubes;
[0011] S3, dispersing attapulgite in deionized water, stirring under heating in a water bath to obtain a attapulgite suspension, adding the modified carbon nanotubes to the attapulgite suspension, stirring under heating in a water bath to obtain a mixed suspension;
[0012] S4, subjecting the mixed suspension to vacuum filtration to induce self-assembly molding, and then drying to obtain a attapulgite-based composite material, i.e., a composite material for industrial wastewater treatment.
[0013] Preferably, in step S1, the molar concentration of ferrous sulfate is 15-18 mmol / L, and the molar concentration of zinc chloride is 12-15 mmol / L;
[0014] The usage ratio of the carbon nanotube, ferrous sulfate, zinc chloride and tetrabutyl titanate solution is (1-3 g): (80-120 mL): (60-80 mL): (20-50 mL).
[0015] Preferably, in step S1, the heating temperature is 70-80°C;
[0016] The calcination temperature is 600-800°C.
[0017] Preferably, in step S2, the mass concentration of the hydrogen peroxide solution is 25-35%;
[0018] Preferably, in step S2, the usage ratio of the iron-zinc-titanium modified carbon nanotubes, carboxymethyl chitosan, dicyclohexylcarbodiimide and N-hydroxysuccinimide is (2-4 g): (3-9 g): (0.05-0.5 g): (0.01-0.2 g).
[0019] Preferably, in step S3, the water bath heating temperature is 55-65°C.
[0020] Preferably, in step S3, the usage ratio of attapulgite and modified carbon nanotubes is (4-8 g): (1-2 g).
[0021] Preferably, in step S4, the vacuum degree is 0.04-0.07 MPa;
[0022] The drying temperature is 40-50°C.
[0023] The present invention also provides a composite material prepared by the above-mentioned preparation method.
[0024] The present invention further proposes an application of the composite material as above, which is applied in industrial wastewater treatment.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The composite material for industrial wastewater treatment provided by the present invention is prepared from low-cost, renewable raw materials such as carbon nanotubes, chitosan and attapulgite, and the preparation method is simple and easy to operate, and is suitable for large-scale production.
[0027] (2) The preparation method of the composite material provided by the present invention comprises the following steps: firstly reacting carbon nanotubes with a metal salt solution to obtain iron, zinc and titanium modified carbon nanotubes, then grafting the carbon nanotubes onto chitosan, and then mixing the carbon nanotubes with attapulgite and subjecting the carbon nanotubes to self-assembly to obtain the composite material. Carbon nanotubes have a high specific surface area and can effectively adsorb pollutants in water. The modification of iron, zinc and titanium further enhances its adsorption characteristics, especially for heavy metal ions such as lead, cadmium, mercury, etc. It has a good removal ability, thereby improving the efficiency of sewage treatment. In addition, the composite material of iron, zinc and titanium can be used as a catalyst to promote the degradation reaction of organic pollutants in water, especially in redox reactions, accelerate the decomposition of pollutants, and reduce the concentration of harmful substances in water. Then, it is modified with carboxymethyl chitosan, which not only increases the dispersibility of the composite material in sewage, but also introduces amino, carboxyl and hydroxyl groups. These functional groups can interact with pollutants in water such as heavy metal ions and organic matter by forming hydrogen bonds and electrostatic effects, significantly improving the removal rate of pollutants in sewage. At the same time, the hydrophobicity and surface activity provided by its polymer chain can promote the aggregation of particulate matter in sewage, thereby improving the sedimentation of sewage, reducing the time required for flocculation, and effectively improving the removal effect of suspended matter in sewage. Finally, through the hydrogen bond self-assembly process, the carbon nanotubes that are not easy to recycle can be attached to attapulgite, improving its recyclability, and can maintain its function in a complex sewage environment, ensuring long-term and effective pollutant treatment capabilities. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a process flow chart of the preparation method of the composite material for industrial wastewater treatment provided by the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.
[0030] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.
[0031] Example 1
[0032] A method for preparing a composite material for industrial wastewater treatment comprises the following steps:
[0033] (1) adding 2 g of carbon nanotubes to a mixed solution of 100 mL of ferrous sulfate with a molar concentration of 16 mmol / L and 70 mL of zinc chloride with a molar concentration of 17 mmol / L, then dropping 35 mL of tetrabutyl titanate solution, heating to 75° C., adding 10 mL of a 2% NaOH solution under stirring, and continuing to stir for a period of time, then filtering, washing, drying, and calcining at 700° C. to obtain iron-zinc-titanium modified carbon nanotubes;
[0034] (2) 3 g of iron-zinc-titanium modified carbon nanotubes were placed in 20 mL of a 30% mass concentration hydrogen peroxide solution and soaked for a period of time, and then 6 g of carboxymethyl chitosan, 0.2 g of dicyclohexylcarbodiimide and 0.1 g of N-hydroxysuccinimide were added, and ultrasonic treatment was performed. The generated product was washed and dried to obtain modified carbon nanotubes;
[0035] (3) dispersing 6 g of attapulgite in 10 mL of deionized water, heating the mixture in a water bath at 60° C. with stirring to obtain a attapulgite suspension, adding 1.5 g of modified carbon nanotubes to the attapulgite suspension, heating the mixture in a water bath at 60° C. with stirring to obtain a mixed suspension;
[0036] (4) The mixed suspension is subjected to vacuum filtration to induce self-assembly molding, and then dried at 45° C. to obtain a attapulgite-based composite material, i.e., a composite material for industrial wastewater treatment.
[0037] Example 2
[0038] A method for preparing a composite material for industrial wastewater treatment comprises the following steps:
[0039] (1) adding 1 g of carbon nanotubes to a mixed solution of 80 mL of ferrous sulfate with a molar concentration of 16 mmol / L and 60 mL of zinc chloride with a molar concentration of 17 mmol / L, then dropping 20 mL of tetrabutyl titanate solution, heating to 75° C., adding 10 mL of a 2% NaOH solution under stirring, and continuing to stir for a period of time, then filtering, washing, drying, and calcining at 600° C. to obtain iron-zinc-titanium modified carbon nanotubes;
[0040] (2) 2 g of iron-zinc-titanium modified carbon nanotubes were placed in 20 mL of a 30% mass concentration hydrogen peroxide solution and soaked for a period of time, and then 3 g of carboxymethyl chitosan, 0.05 g of dicyclohexylcarbodiimide and 0.01 g of N-hydroxysuccinimide were added, and ultrasonic treatment was performed. The generated product was washed and dried to obtain modified carbon nanotubes;
[0041] (3) dispersing 4 g of attapulgite in 10 mL of deionized water, heating the mixture in a water bath at 60° C. with stirring to obtain a attapulgite suspension, adding 1 g of the modified carbon nanotubes to the attapulgite suspension, heating the mixture in a water bath at 60° C. with stirring to obtain a mixed suspension;
[0042] (4) The mixed suspension is subjected to vacuum filtration to induce self-assembly molding, and then dried at 40° C. to obtain a attapulgite-based composite material, i.e., a composite material for industrial wastewater treatment.
[0043] Example 3
[0044] A method for preparing a composite material for industrial wastewater treatment comprises the following steps:
[0045] (1) 3 g of carbon nanotubes were added to a mixed solution of 120 mL of ferrous sulfate with a molar concentration of 16 mmol / L and 80 mL of zinc chloride with a molar concentration of 17 mmol / L, and then 50 mL of tetrabutyl titanate solution was added dropwise, heated to 80° C., 10 mL of a 2% NaOH solution was added under stirring, and stirring was continued for a period of time, and then filtered, washed, dried, and calcined at 800° C. to obtain iron-zinc-titanium modified carbon nanotubes;
[0046] (2) 4 g of iron-zinc-titanium modified carbon nanotubes were placed in 20 mL of a 30% mass concentration hydrogen peroxide solution and soaked for a period of time, and then 9 g of carboxymethyl chitosan, 0.5 g of dicyclohexylcarbodiimide and 0.2 g of N-hydroxysuccinimide were added, and ultrasonic treatment was performed. The generated product was washed and dried to obtain modified carbon nanotubes;
[0047] (3) dispersing 8 g of attapulgite in 10 mL of deionized water, heating the mixture in a water bath at 60° C. with stirring to obtain a attapulgite suspension, adding 2 g of modified carbon nanotubes to the attapulgite suspension, heating the mixture in a water bath at 60° C. with stirring to obtain a mixed suspension;
[0048] (4) The mixed suspension is subjected to vacuum filtration to induce self-assembly molding, and then dried at 50° C. to obtain a attapulgite-based composite material, i.e., a composite material for industrial wastewater treatment.
[0049] Comparative Example 1
[0050] A method for preparing a composite material for industrial wastewater treatment comprises the following steps:
[0051] (1) adding 2 g of carbon nanotubes to a mixed solution of 100 mL of ferrous sulfate with a molar concentration of 16 mmol / L and 70 mL of zinc chloride with a molar concentration of 17 mmol / L, heating to 75° C., adding 10 mL of a 2% NaOH solution under stirring, and continuing stirring for a period of time, then filtering, washing, drying, and calcining at 700° C. to obtain iron-zinc modified carbon nanotubes;
[0052] (2) 3 g of iron-zinc-modified carbon nanotubes were placed in 20 mL of a 30% hydrogen peroxide solution and soaked for a period of time, and then 6 g of carboxymethyl chitosan, 0.2 g of dicyclohexylcarbodiimide and 0.1 g of N-hydroxysuccinimide were added, and ultrasonic treatment was performed. The generated product was washed and dried to obtain modified carbon nanotubes;
[0053] (3) dispersing 6 g of attapulgite in 10 mL of deionized water, heating the mixture in a water bath at 60° C. with stirring to obtain a attapulgite suspension, adding 1.5 g of modified carbon nanotubes to the attapulgite suspension, heating the mixture in a water bath at 60° C. with stirring to obtain a mixed suspension;
[0054] (4) The mixed suspension is subjected to vacuum filtration to induce self-assembly molding, and then dried at 45° C. to obtain a attapulgite-based composite material, i.e., a composite material for industrial wastewater treatment.
[0055] Compared with Example 1, the carbon nanotubes of Comparative Example 1 were not mixed with the tetrabutyl titanate solution.
[0056] Comparative Example 2
[0057] A method for preparing a composite material for industrial wastewater treatment comprises the following steps:
[0058] (1) 3 g of carbon nanotubes were placed in 20 mL of a 30% hydrogen peroxide solution and soaked for a period of time, and then 6 g of carboxymethyl chitosan, 0.2 g of dicyclohexylcarbodiimide and 0.1 g of N-hydroxysuccinimide were added, and ultrasonic treatment was performed. The generated product was washed and dried to obtain modified carbon nanotubes;
[0059] (2) dispersing 6 g of attapulgite in 10 mL of deionized water, heating the mixture in a water bath at 60° C. with stirring to obtain a attapulgite suspension, adding 1.5 g of modified carbon nanotubes to the attapulgite suspension, heating the mixture in a water bath at 60° C. with stirring to obtain a mixed suspension;
[0060] (3) The mixed suspension is subjected to vacuum filtration to induce self-assembly molding, and then dried at 45° C. to obtain a attapulgite-based composite material, i.e., a composite material for industrial wastewater treatment.
[0061] Compared with Example 1, the carbon nanotubes in Comparative Example 2 are not modified with iron, zinc and titanium.
[0062] Comparative Example 3
[0063] A method for preparing a composite material for industrial wastewater treatment comprises the following steps:
[0064] (1) adding 2 g of carbon nanotubes to a mixed solution of 100 mL of ferrous sulfate with a molar concentration of 16 mmol / L and 70 mL of zinc chloride with a molar concentration of 17 mmol / L, then dropping 35 mL of tetrabutyl titanate solution, heating to 75° C., adding 10 mL of a 2% NaOH solution under stirring, and continuing to stir for a period of time, then filtering, washing, drying, and calcining at 700° C. to obtain iron-zinc-titanium modified carbon nanotubes;
[0065] (2) 3 g of iron-zinc-titanium modified carbon nanotubes were placed in 20 mL of a 30% mass concentration hydrogen peroxide solution and soaked for a period of time, and then 0.2 g of dicyclohexylcarbodiimide and 0.1 g of N-hydroxysuccinimide were added, and ultrasonic treatment was performed. The generated product was washed and dried to obtain a solid;
[0066] (3) dispersing 6 g of attapulgite in 10 mL of deionized water, heating the mixture in a water bath at 60° C. with stirring to obtain a attapulgite suspension, adding 1.5 g of the solid to the attapulgite suspension, heating the mixture in a water bath at 60° C. with stirring to obtain a mixed suspension;
[0067] (4) The mixed suspension is subjected to vacuum filtration to induce self-assembly molding, and then dried at 45° C. to obtain a attapulgite-based composite material, i.e., a composite material for industrial wastewater treatment.
[0068] Compared with Example 1, the iron-zinc-titanium modified carbon nanotubes of Comparative Example 3 did not react with chitosan.
[0069] Comparative Example 4
[0070] A method for preparing a composite material for industrial wastewater treatment comprises the following steps:
[0071] (1) adding 2 g of carbon nanotubes to a mixed solution of 100 mL of ferrous sulfate with a molar concentration of 16 mmol / L and 70 mL of zinc chloride with a molar concentration of 17 mmol / L, then dropping 35 mL of tetrabutyl titanate solution, heating to 75° C., adding 10 mL of a 2% NaOH solution under stirring, and continuing to stir for a period of time, then filtering, washing, drying, and calcining at 700° C. to obtain iron-zinc-titanium modified carbon nanotubes;
[0072] (2) 3 g of iron-zinc-titanium modified carbon nanotubes were placed in 20 mL of 30% hydrogen peroxide solution and soaked for a period of time, and then 6 g of carboxymethyl chitosan, 0.2 g of dicyclohexylcarbodiimide and 0.1 g of N-hydroxysuccinimide were added, and ultrasonic treatment was performed. The generated product was washed and dried to obtain modified carbon nanotubes.
[0073] Compared with Example 1, the modified carbon nanotubes of Comparative Example 4 were not subjected to self-assembly molding treatment with attapulgite.
[0074] Test methods and results
[0075] Test Example 1
[0076] Prepare As with an initial concentration of 500 mg / L 3+ Cr 3+ , Pb 2+ 、Ni + , Hg 2+ A metal ion aqueous solution was prepared to simulate chemical heavy metal wastewater, and then the composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were used for treatment (the mass volume ratio of the composite material to the heavy metal wastewater was 1 g: 1 L). After the treatment was completed (temperature 25°C, treatment time 30 minutes), the filtrate was filtered to obtain the filtrate. The metal ion concentration of the filtrate and the heavy metal wastewater before treatment was analyzed and detected by flame atomic absorption spectrophotometry, and then the adsorption amount of the composite material, that is, the mass of metal ions adsorbed by the unit mass of the composite material, was calculated. The results are shown in Table 1.
[0077] Table 1 Adsorption statistics
[0078]
[0079] Test Example 2
[0080] Taking the wastewater of a metallurgical and chemical plant as an example, the influent water quality is as follows: the chemical oxygen demand (COD) concentration is 4259 mg / L, the metal ions (including As 3+ Cr 3+ , Pb 2+ 、Ni + , Hg 2+ ) total content was 23535 mg / L, and the composite materials of Examples 1 to 3 and Comparative Examples 1 to 3 were used for treatment respectively (the mass volume ratio of the composite material to the wastewater was 1 g: 1 L, the temperature was 25°C, and the treatment time was 30 minutes), and the effluent water quality was shown in Table 2. Among them, the metal ion content before treatment was detected by EDTA complexometric titration, and the metal ion content after treatment was determined by atomic absorption spectroscopy.
[0081] Table 2 Water quality of effluent
[0082]
[0083]
[0084] Test Example 3
[0085] The reaction solution of the above-mentioned Test Example 2 was allowed to stand and precipitate, and then the solid-liquid separation was performed to separate the composite material solid adsorbed with heavy metal ions and dried at 80°C for 36 hours to constant weight, and then the composite material solid was washed with a disodium salt solution of ethylenediaminetetraacetic acid having a molar concentration of 0.02 mol / L to desorb the heavy metal ions; then the solid was separated by precipitation again and dried at 80°C for 36 hours, and the recovery rate was calculated by weighing to obtain Table 3.
[0086] Table 3 Recovery rate table
[0087] Group Recovery rate (%) Example 1 92% Example 2 89% Example 3 90% Comparative Example 1 72% Comparative Example 2 68% Comparative Example 3 31% Comparative Example 4 19%
[0088] As shown in Table 1, compared with Comparative Examples 1 to 4, the composite materials provided in Examples 1 to 3 of the present invention have a high affinity for heavy metal ions As. 3+ Cr 3+ , Pb 2+ 、Ni + , Hg 2+ All have good adsorption capacity; it can be seen from Table 2 that the composite materials provided by Examples 1 to 3 of the present invention can effectively reduce COD and metal ion content; it can be seen from Table 3 that the composite materials provided by Examples 1 to 3 of the present invention have a high recovery rate and can be reused.
[0089] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.
Claims
1. A method for preparing a composite material for industrial wastewater treatment, characterized in that: The following steps are involved: S1, adding carbon nanotubes to a mixed solution of ferrous sulfate and zinc chloride, then dropping a tetrabutyl titanate solution, heating, adding a NaOH solution under stirring, and continuing to stir for a period of time, then filtering, washing, drying, and calcining to obtain iron-zinc-titanium modified carbon nanotubes; S2, soaking the iron-zinc-titanium modified carbon nanotubes in a hydrogen peroxide solution for a period of time, then adding carboxymethyl chitosan, dicyclohexylcarbodiimide and N-hydroxysuccinimide, ultrasonically treating, washing and drying the generated product to obtain modified carbon nanotubes; S3, dispersing attapulgite in deionized water, stirring under heating in a water bath to obtain a attapulgite suspension, adding the modified carbon nanotubes to the attapulgite suspension, stirring under heating in a water bath to obtain a mixed suspension; S4, subjecting the mixed suspension to vacuum filtration to induce self-assembly molding, and then drying to obtain a attapulgite-based composite material, i.e., a composite material for industrial wastewater treatment.
2. The method for preparing a composite material for industrial wastewater treatment according to claim 1, characterized in that: In step S1, the molar concentration of ferrous sulfate is 15-18 mmol / L, and the molar concentration of zinc chloride is 12-15 mmol / L; The usage ratio of the carbon nanotube, ferrous sulfate, zinc chloride and tetrabutyl titanate solution is (1-3 g): (80-120 mL): (60-80 mL): (20-50 mL).
3. The method for preparing a composite material for industrial wastewater treatment according to claim 1, characterized in that: In step S1, the heating temperature is 70-80°C; The calcination temperature is 600-800°C.
4. The method for preparing a composite material for industrial wastewater treatment according to claim 1, characterized in that: In step S2, the mass concentration of the hydrogen peroxide solution is 25-35%.
5. The method for preparing a composite material for industrial wastewater treatment according to claim 1, characterized in that: In step S2, the usage ratio of the iron-zinc-titanium modified carbon nanotubes, carboxymethyl chitosan, dicyclohexylcarbodiimide and N-hydroxysuccinimide is (2-4 g): (3-9 g): (0.05-0.5 g): (0.01-0.2 g).
6. The method for preparing a composite material for industrial wastewater treatment according to claim 1, characterized in that: In step S3, the water bath is heated at a temperature of 55-65°C.
7. The method for preparing a composite material for industrial wastewater treatment according to claim 1, characterized in that: In step S3, the usage ratio of attapulgite and modified carbon nanotubes is (4-8 g): (1-2 g).
8. The method for preparing a composite material for industrial wastewater treatment according to claim 1, characterized in that: In step S4, the vacuum degree is 0.04-0.07 MPa; The drying temperature is 40-50°C.
9. A composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the composite material according to claim 9, characterized in that: Used in industrial wastewater treatment.
Citation Information
Patent Citations
Magnetic Ce1-xSmxO2-delta / attapulgite nano composite preparation method
CN104785268A
Carbon nanotube printing and dyeing wastewater treatment complexing agent based on SiO<2> / TiO<2> mesoporous composite microsphere carrier and preparation method
CN105327683A
Preparation method of amino modified chitosan composite adsorbing material
CN106268673A
Preparation method and application of activated carbon based inorganic-organic composite material
CN107213881A
Preparation method of zinc oxide-carbon nanotube composite material
CN107552035A